1987
DOI: 10.1177/000841748705400308
|View full text |Cite
|
Sign up to set email alerts
|

Measurement in Occupational Therapy: Scientific Criteria for Evaluation

Abstract: Measurement instruments are used by occupational therapists to describe patients, predict recovery and evaluate immediate treatment effect within their clinical practice. An instrument's development and methodological properties are guided by the purpose of the instrument. In this paper, criteria are proposed for evaluating the utility of measurement tools used by occupational therapists. These criteria are discussed within the framework of the intended use of the instrument. The criteria include the instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(105 citation statements)
references
References 8 publications
(16 reference statements)
1
101
1
Order By: Relevance
“…Assessment has to take place for this to be possible. Standardised assessment provides quantitative information, useful for tracking the client's progress and demonstrating the outcome of therapy 1 . However, research studies have shown that standardised assessments are often not used routinely in practice.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment has to take place for this to be possible. Standardised assessment provides quantitative information, useful for tracking the client's progress and demonstrating the outcome of therapy 1 . However, research studies have shown that standardised assessments are often not used routinely in practice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Assessment is an integral part of the occupational therapy process and a necessity for evidence based practice 1 . Without appropriate measurement, therapists cannot provide evidence for interventions offered.…”
Section: Introductionmentioning
confidence: 99%
“…13,19 The goniometer, KT- measure. 15 However, differences in outcome measurement time frames and interpretation did not allow for a meta-analysis of the outcome data.…”
Section: Discussionmentioning
confidence: 99%
“…Intraclass correlation coefficients (Shrout & Fleiss, 1979) were used to analyse the continuous variables in the CIQ and SF-36. An ICC coefficient of 0.65 or higher is considered reasonable (Law, 1987). Statistical significance was not calculated for the ICC or kappa coefficients as sample size influences it so greatly.…”
Section: Statistical Analysesmentioning
confidence: 99%